Inclusive Quality Education in Rural Areas: A Case Study of Ledug Pintar - Fatur, Fatur Fahrezi; Rohmah, Lailatu; Shodiq, Muhammad Ja’far (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study explores how inclusive quality education can be realized in rural areas through a grassroots edupreneurship model. It addresses a gap in current literature by examining how community-led educational initiatives can offer equitable and sustainable learning alternatives outside formal systems in underserved regions.Method – A qualitative case study was conducted in Ledug Village, Banyumas Regency, utilizing participatory observation, in-depth interviews, and document analysis. Data were analyzed using the Miles and Huberman framework, involving data condensation, display, and conclusion drawing. Findings – The Ledug Pintar initiative presents a model of inclusive and flexible learning that accommodates children, youth, and elderly learners in a rural context. By merging educational goals with community-based social entrepreneurship, it provides affordable and accessible services that promote inclusive education at the village level. Key strengths include youth leadership, local relevance, and intergenerational access to learning. Research Implications – This study highlights the potential of community-driven approaches to achieving inclusive quality education in rural areas. It suggests practical implications for local governments and NGOs to support similar models in other underserved contexts. However, findings remain context-bound, and further research is required to evaluate transferability and long-term outcomes.